Early peroral feeding after pancreaticoduodenecomy - A. V. Skums; V. O. Kuzmenko; A. A. Skums; N. R. Prysyazhna (Клінічна хірургія)
Objective. To analyze the various ways for enteral feeding after pancreaticoduodenectomy.